Low temperature heat treatments on Ti-15Zr-xMo alloys - Xavier, Caio Castanho [UNESP]; Correa, Diego Rafael Nespeque [UNESP]; Grandini, Carlos Roberto [UNESP]; Rocha, Luís Augusto [UNESP] (Elsevier, 2017)
This paper regards the study of the effect of heat treatments on the microstructure and microhardness of Ti-15Zr-xMo alloys aimed to biomedical applications. The alloys were melted in an arc-furnace, with four different compositions in order to obtain samples with α′, α′+β and β phase microstructures. The as-cast alloys exhibited a full lamellar structure for the Ti-15Zr, a bimodal structure composed by β phase grains along with an α phase acicular structure at the grain boundaries for the Ti-15Zr-5Mo, predominant β phase for the Ti-15Zr-10Mo and only β phase for the Ti-15Zr-15Mo. Results showed that both microstructure and mechanical properties of the studied alloys can be tailored by relatively low temperature heat treatments, as they resulted in the growth of the α′ phase in all alloys. The formation of α′ phase resulted in a decrease in the microhardness of the alloys.
Keywords: Alloys; Biomaterials; Heat treatment; Titanium